2022
DOI: 10.3389/fpubh.2022.872648
|View full text |Cite
|
Sign up to set email alerts
|

The Awareness of Rare Diseases Among Medical Students and Practicing Physicians in the Republic of Kazakhstan. An Exploratory Study

Abstract: Although national plans or strategies for rare diseases (RDs) have been implemented in many jurisdictions research show that one of the main barriers RD patients face during medical encounter is medical professionals' low level of knowledge and experience on the diagnosis, treatment and rehabilitation of RD patients. Consequently, there is a need to increase the standards of medical education in the field of RDs and to revise the undergraduate and postgraduate training programs. However, while studies on medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…For example, research carried out in La Rioja, Spain concluded that future healthcare and non-healthcare professionals have a low level of general knowledge of this subject and none of them prioritize the allocation of funds to RDs (7). Also, another study conducted in Kazakhstan showed deficient knowledge if the epidemiology of RDs, since only 5% of the physicians had mastered the frequency of prevalence and correctly estimated the number of RDs (19). In this research, 92% of the students and 85.6% of the physicians obtained scores indicative of an insufficient or low level of knowledge, as demonstrated in a study carried out in Spain, where the primary health care professionals lack knowledge about RDs and this lack is consciously perceived by physicians (20).…”
Section: Discussionmentioning
confidence: 99%
“…For example, research carried out in La Rioja, Spain concluded that future healthcare and non-healthcare professionals have a low level of general knowledge of this subject and none of them prioritize the allocation of funds to RDs (7). Also, another study conducted in Kazakhstan showed deficient knowledge if the epidemiology of RDs, since only 5% of the physicians had mastered the frequency of prevalence and correctly estimated the number of RDs (19). In this research, 92% of the students and 85.6% of the physicians obtained scores indicative of an insufficient or low level of knowledge, as demonstrated in a study carried out in Spain, where the primary health care professionals lack knowledge about RDs and this lack is consciously perceived by physicians (20).…”
Section: Discussionmentioning
confidence: 99%
“…The results of a study conducted in Kazakhstan show that medical students and physicians suffer from inadequate education in rare diseases. They suggested an immediate revision of medical education standards [21].…”
Section: Discussionmentioning
confidence: 99%
“…This may be a result of a lack of awareness among HCPs in knowing what matters to patients with specific rare disorders. Recent studies of primary and secondary care providers in Kazakhstan ( 32 ), the United Kingdom ( 12 ) and Poland ( 33 ) have demonstrated that most physicians lacked basic knowledge about the aetiology, epidemiology and prevalence of rare conditions, with 94.6% of physicians perceiving their knowledge on rare disorders as insufficient or very poor, and less than 5.3% feeling prepared for caring for patients with rare disorders ( 33 ). Co-design between patients and HCPs may help broaden current understanding and better align these stakeholder perspectives and expectations with regard to data collection and sharing.…”
Section: Discussionmentioning
confidence: 99%